2022
DOI: 10.1186/s13018-022-03155-9
|View full text |Cite
|
Sign up to set email alerts
|

Modified donor blood flow-preserved cross-leg anterolateral thigh flap procedure for complex lower extremity reconstruction

Abstract: Background Complex lower limb reconstruction due to severe trauma remains a challenge for reconstructive surgeons. Here, we introduce a modified donor blood flow-preserved cross-leg anterolateral thigh flap procedure and evaluate its clinical efficacy. Methods Between January 2013 and December 2019, 22 patients (range 10 to 64 years old) with unilateral lower limb injury underwent modified donor blood flow-preserved cross-leg anterolateral thigh fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, it is difficult to prepare a segment of Y-shaped or T-shaped arterial bifurcation during the harvest of free latissimus dorsi flap. 14,35 Yu et al suggested an alternative option to preserve integrity of the recipient vessel which is an end-to-side anastomoses to the contralateral limb in order to maintain continuity of the distal blood flow, although they performed the microvascular anastomoses of their cross-leg bridge free flaps series in an end-to-end fashion. 11 Several previous studies have reported the use of end-to-side anastomosis to recipient vessels in the same injured leg to preserve the leg vascular flow and reported no significant difference in the rate of flap complications between the outcome of end-toend and end-to-side anastomoses in free flap reconstruction of lower limb defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is difficult to prepare a segment of Y-shaped or T-shaped arterial bifurcation during the harvest of free latissimus dorsi flap. 14,35 Yu et al suggested an alternative option to preserve integrity of the recipient vessel which is an end-to-side anastomoses to the contralateral limb in order to maintain continuity of the distal blood flow, although they performed the microvascular anastomoses of their cross-leg bridge free flaps series in an end-to-end fashion. 11 Several previous studies have reported the use of end-to-side anastomosis to recipient vessels in the same injured leg to preserve the leg vascular flow and reported no significant difference in the rate of flap complications between the outcome of end-toend and end-to-side anastomoses in free flap reconstruction of lower limb defects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is difficult to prepare a segment of Y-shaped or T-shaped arterial bifurcation during the harvest of free latissimus dorsi flap. 14 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding lower limb reconstructions, the conventional autonomization delay is considered to be slightly longer. Even if some authors have described earlier time points [71], the cross-leg flap is mostly divided after at least 4 weeks [15][16][17], even in the most recent case series [18,[72][73][74][75]. Modern technologies have brought interesting applications to the study of flap autonomization.…”
Section: Partmentioning
confidence: 99%